A method for improving solubility of curcumin in water and application thereof
Patent Information
- Application Number
- CN202411517301.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-10-29
AI Technical Summary
[0004]尽管姜黄素是传统的最鲜艳的天然黄色染料之一,但由于其在水中几乎不溶,因而在对织物进行染色时的上染率低、色牢度差这大大限制了该天然色素的染色应用
[0021] (1) The present invention uses cationic modified nanocellulose to improve the solubility of curcumin in water, which provides the possibility for the dyeing application of curcumin in textiles.
Smart Images

Figure CN119392512B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of textile technology, and specifically discloses a method and application for improving the solubility of curcumin in water. Background Technology
[0002] Curcumin is a polyphenolic compound extracted from plants of the genus Curcuma. It possesses various physiological and pharmacological activities, including antibacterial, antitumor, anti-inflammatory, antioxidant, and free radical scavenging activities. It is a natural yellow pigment with high safety (no obvious toxic side effects on humans at a dose of 12g / day) and good heat resistance. Curcumin is soluble in organic solvents such as methanol, ethanol, acetone, and chloroform, but its water solubility is very low, limiting its application in water-soluble matrices in food, pharmaceuticals, textiles, and other related fields.
[0003] Currently, the main methods to improve the water solubility of curcumin include: solid dispersion technology, inclusion technology, emulsification technology, microencapsulation technology, and nanocarrier technologies such as liposomes, polymer nanoparticles, and polymer micelles. These methods mostly use formulation technology to improve the solubility, stability, and bioavailability of curcumin, and expand its application in the pharmaceutical field. However, these methods are not applicable in the field of textile dyeing.
[0004] Although curcumin is one of the most vibrant natural yellow dyes, its near insolubility in water results in low dyeing rates and poor colorfastness, significantly limiting its application in fabric dyeing. While mordant dyeing can improve some dyeing indicators such as the dyeing rate and colorfastness of natural curcumin to a certain extent, the use of heavy metal mordants not only causes severe pollution during the dyeing and finishing process, but the heavy metals remaining on the fabric are also harmful to human health. Furthermore, mordated fabrics exhibit noticeable color differences. Although there have been reports in recent years of using low-toxicity rare earth salts to replace traditional heavy metal salts as mordants, this dyeing method wastes my country's precious rare earth resources. Summary of the Invention
[0005] To overcome the shortcomings of existing curcumin staining techniques, this invention provides a method for improving the solubility of curcumin in water. The method uses microcrystalline cellulose as raw material, prepares nanocellulose by sulfuric acid hydrolysis, and then performs cation modification of the nanocellulose with 3-chloro-2-hydroxypropyltrimethylammonium chloride. The curcumin powder is mixed and stirred with the cation-modified nanocellulose solution, centrifuged, and a small amount of insoluble matter is removed to obtain an aqueous solution of solubilized curcumin.
[0006] The method for improving the solubility of curcumin in water provided by this invention specifically includes the following steps:
[0007] (1) Slowly add microcrystalline cellulose to a sulfuric acid solution of a certain mass fraction, react at a certain temperature for a certain time, centrifuge, wash the precipitate with deionized water until neutral, dry and set aside;
[0008] The reaction mixture consisted of a sulfuric acid solution with a mass fraction of 55-66%; a mass-to-volume ratio (g / mL) of microcrystalline cellulose to sulfuric acid solution of 1:9.75-1:7.25; a reaction temperature of 35-60℃; and a reaction time of 90-150 min.
[0009] (2) The nanocellulose obtained in step (1) is ultrasonically dispersed in deionized water, a cationic modifier is added, the pH of the solution is adjusted to 12 with 4 mol / L sodium hydroxide solution, the reaction is carried out at a certain temperature for a certain time, centrifuged, the precipitate is washed with deionized water until neutral, dried and set aside.
[0010] The concentration of nanocellulose in deionized water is 1 g / L-6 g / L, and the cationic modifier is 3-chloro-2-hydroxypropyltrimethylammonium chloride, with a mass fraction of 0.5-3% in the solution.
[0011] The reaction temperature is 55-80℃, and the reaction time is 90-330 min.
[0012] (3) Disperse the cationic modified nanocellulose obtained in step (2) in water, add curcumin, stir at room temperature for a certain time, and centrifuge to obtain a solubilized curcumin solution.
[0013] The concentration of cationic modified nanocellulose in water was 1-2.67 g / L, the mass ratio of cationic modified nanocellulose to curcumin was 7.92:1-3:1, and the stirring time was 12-36 h.
[0014] Another objective of this invention is to overcome the shortcomings of the prior art by providing an application of cationic modified nanocellulose solubilized curcumin in textile coloring.
[0015] The cotton fabric was immersed in a cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30 and kept at 55℃-80℃ for 30min-90min. After dyeing, the fabric was removed, washed and dried.
[0016] To improve the dyeing depth and binding fastness of curcumin on cotton fabrics, this invention provides a method for modifying and pretreating cotton fabrics and fixing the color, specifically as follows:
[0017] Prepare a 35% citric acid solution. Weigh a certain amount of sodium hypophosphite and dissolve it in the citric acid solution, with the sodium hypophosphite having a mass fraction of 10%. Immerse cotton fabric in the above mixed solution at a liquor ratio of 1:25. Stir at room temperature for 15 minutes, then dry at 80℃ for 10 minutes. Afterward, wash thoroughly with deionized water and dry at 40℃ to obtain modified cotton fabric. Then, immerse the modified cotton fabric in a cationic modified nanocellulose solubilized curcumin solution at a liquor ratio of 1:30 and keep it at 55℃-80℃ for 30-90 minutes. After dyeing, remove the fabric, wash and dry it to obtain citric acid-sodium hypophosphite modified dyed cotton fabric.
[0018] Dissolve chitosan in a 2% (w / w) acetic acid solution to prepare a 1% (w / w) chitosan solution. Immerse the citric acid-sodium hypophosphite modified dyed cotton fabric in the chitosan solution, with a mass ratio of dyed cotton fabric to chitosan solution of 1:100. After immersing at room temperature for 15 minutes, dry at 150°C for 15 minutes.
[0019] This invention utilizes the acidity of sulfuric acid to hydrolyze the amorphous and partially crystalline regions of microcrystalline cellulose, causing partial breakage of the molecular chains and forming nanoscale cellulose particles that are stably dispersed in water. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride provides positively charged groups to the nanocellulose, allowing it to form hydrogen bonds and electrostatic bonds with curcumin, thus increasing the solubility of curcumin in water. The cationic nanocellulose-curcumin complex can form hydrogen bonds and ionic bonds with the hydroxyl groups on cellulose, which is beneficial for its coloring of textiles. Furthermore, carboxylating cotton fabrics can further improve the dyeing depth of the cationic nanocellulose-curcumin complex on cotton fabrics; and utilizing the film-forming properties of the natural cationic polymer chitosan on cotton fabrics further improves the color fastness of curcumin-dyed cotton fabrics.
[0020] The beneficial effects of this invention are as follows:
[0021] (1) The present invention uses cationic modified nanocellulose to improve the solubility of curcumin in water, which provides the possibility for the dyeing application of curcumin in textiles.
[0022] (2) The present invention further improves the color depth of cotton fabric dyed with cationic nanocellulose-curcumin complex by carboxylation modification of cotton fabric.
[0023] (3) The present invention utilizes the natural cationic polymer chitosan to fix the color of cotton fabric dyed with solubilized curcumin, thereby further improving its color fastness. Attached image description:
[0024] Figure 1Photographs of nanocellulose-solubilized curcumin solutions obtained in Examples 1(A), 1(B), 2(C), 3(D), 4(E), 5(F), 2(G), 3(H), 4(I), 5(J), 6(K), 7(L), and 8(M).
[0025] Figure 2 The concentration of curcumin in the nanocellulose-solubilized curcumin solutions obtained in Examples 1, 4, 5, 6, 7, 8 and Comparative Examples 1 and 2.
[0026] Figure 3 The images show color comparisons of cotton fabrics dyed with nanocellulose-solubilized curcumin solutions obtained in Examples 1, 2, 3, 4, 5, 6, 7, 8, 10, 11 and Comparative Examples 1 and 2, 3, 4, 5 before and after washing. Detailed Implementation
[0027] The present invention will now be described in further detail with reference to specific embodiments. It should be understood that these embodiments are merely illustrative of the invention and are not intended to limit the scope of the invention in any way.
[0028] Example 1
[0029] (1) Slowly add microcrystalline cellulose to a 64% sulfuric acid solution. The mass-volume ratio of microcrystalline cellulose to sulfuric acid solution is 1:8.75 (g / mL). After reacting at 45℃ for 110 min, centrifuge, wash the precipitate with deionized water until neutral, dry and set aside.
[0030] (2) The nanocellulose obtained in step (1) was ultrasonically dispersed in deionized water to prepare a nanocellulose suspension with a concentration of 3 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the solution was 1.5%. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution. The reaction was carried out at 65°C for 270 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried and set aside.
[0031] (3) Disperse the 49.2 mg cationic modified nanocellulose obtained in step (2) in 30 ml of water, add 10 mg curcumin, stir at room temperature for 24 h, and centrifuge to obtain a solubilized curcumin solution.
[0032] (4) Immerse the cotton fabric in the above cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30, keep it at 70℃ for 60 minutes, and after dyeing, take out the fabric, wash and dry it.
[0033] Comparative Example 1
[0034] Disperse 49.2 mg of microcrystalline cellulose in 30 ml of water, add 10 mg of curcumin, stir at room temperature for 24 h, centrifuge to obtain microcrystalline cellulose-infused curcumin solution; immerse cotton fabric in the above curcumin solution at a bath ratio of 1:30, keep warm at 70℃ for 60 min, after dyeing, remove the fabric, wash and dry.
[0035] Comparative Example 2
[0036] Microcrystalline cellulose was ultrasonically dispersed in deionized water to prepare a 3 g / L microcrystalline cellulose suspension. A cationic modifier, 3-chloro-2-hydroxypropyltrimethylammonium chloride (3-chloro-2-hydroxypropyltrimethylammonium chloride with a mass fraction of 1.5%), was added. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution, and the mixture was reacted at 65°C for 270 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried, and set aside. 49.2 mg of modified microcrystalline cellulose was dispersed in 30 ml of water, and 10 mg of curcumin was added. The mixture was stirred at room temperature for 24 h, then centrifuged to obtain a solubilized curcumin solution. Cotton fabric was immersed in the modified microcrystalline cellulose solubilized curcumin solution at a 1:30 bath ratio and kept at 70°C for 60 min. After dyeing, the fabric was removed, washed, and dried.
[0037] Comparative Example 3
[0038] 49.2 mg of the nanocellulose prepared in Example 1 was dispersed in 30 ml of water, and 10 mg of curcumin was added. The mixture was stirred at room temperature for 24 h, and then centrifuged to obtain a nanocellulose-enriched curcumin solution. Cotton fabric was immersed in the above curcumin solution at a bath ratio of 1:30 and kept at 70°C for 60 min. After dyeing, the fabric was removed, washed, and dried.
[0039] Comparative Example 4
[0040] The nanocellulose prepared in Comparative Example 1 was ultrasonically dispersed in deionized water to prepare a microcrystalline cellulose suspension with a concentration of 3 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added, with a mass fraction of 0.2% in the solution. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution, and the mixture was reacted at 65°C for 270 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried, and set aside. 49.2 mg of modified microcrystalline cellulose was dispersed in 30 ml of water, and 10 mg of curcumin was added. The mixture was stirred at room temperature for 24 h, and then centrifuged to obtain a solubilized curcumin solution. Cotton fabric was immersed in the above modified microcrystalline cellulose solubilized curcumin solution at a bath ratio of 1:30 and kept at 70°C for 60 min. After dyeing, the fabric was removed, washed, and dried.
[0041] Comparative Example 5
[0042] The nanocellulose prepared in Example 1 was ultrasonically dispersed in deionized water to prepare a microcrystalline cellulose suspension with a concentration of 3 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added, with a mass fraction of 3.4% in the solution. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution, and the mixture was reacted at 65°C for 270 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried, and set aside. 49.2 mg of modified microcrystalline cellulose was dispersed in 30 ml of water, and 10 mg of curcumin was added. The mixture was stirred at room temperature for 24 h, and then centrifuged to obtain a solubilized curcumin solution. Cotton fabric was immersed in the above modified microcrystalline cellulose solubilized curcumin solution at a bath ratio of 1:30 and kept at 70°C for 60 min. After dyeing, the fabric was removed, washed, and dried.
[0043] Example 2
[0044] The nanocellulose prepared in Example 1 was ultrasonically dispersed in deionized water to prepare a microcrystalline cellulose suspension with a concentration of 3 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added, with a mass fraction of 0.5% in the solution. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution, and the mixture was reacted at 65°C for 270 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried, and set aside. 49.2 mg of modified microcrystalline cellulose was dispersed in 30 ml of water, and 10 mg of curcumin was added. The mixture was stirred at room temperature for 24 h, and then centrifuged to obtain a solubilized curcumin solution. Cotton fabric was immersed in the above modified microcrystalline cellulose solubilized curcumin solution at a bath ratio of 1:30 and kept at 70°C for 60 min. After dyeing, the fabric was removed, washed, and dried.
[0045] Example 3
[0046] The nanocellulose prepared in Example 1 was ultrasonically dispersed in deionized water to prepare a microcrystalline cellulose suspension with a concentration of 3 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added, with a mass fraction of 3.0% in the solution. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution, and the mixture was reacted at 65°C for 270 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried, and set aside. 49.2 mg of modified microcrystalline cellulose was dispersed in 30 ml of water, and 10 mg of curcumin was added. The mixture was stirred at room temperature for 24 h, and then centrifuged to obtain a solubilized curcumin solution. Cotton fabric was immersed in the above modified microcrystalline cellulose solubilized curcumin solution at a bath ratio of 1:30 and kept at 70°C for 60 min. After dyeing, the fabric was removed, washed, and dried.
[0047] Example 4
[0048] (1) Slowly add microcrystalline cellulose to a 55% sulfuric acid solution with a mass-volume ratio of microcrystalline cellulose to sulfuric acid solution of 1:9.75 (g / mL). After reacting at 35°C for 150 min, centrifuge, wash the precipitate with deionized water until neutral, dry and set aside.
[0049] (2) The nanocellulose obtained in step (1) was ultrasonically dispersed in deionized water to prepare a nanocellulose suspension with a concentration of 1 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the solution was 0.5%. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution. The reaction was carried out at 55℃ for 330 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried and set aside.
[0050] (3) Disperse 30 mg of the cationic modified nanocellulose obtained in step (2) in 30 ml of water, add 10 mg of curcumin, stir at room temperature for 36 h, and centrifuge to obtain a solubilized curcumin solution.
[0051] (4) Immerse the cotton fabric in the above cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30, keep it at 55℃ for 90 minutes, and after dyeing, take out the fabric, wash and dry it.
[0052] Example 5
[0053] (1) Slowly add microcrystalline cellulose to a 58% sulfuric acid solution with a mass-volume ratio of microcrystalline cellulose to sulfuric acid solution of 1:9.25 (g / mL). After reacting at 40℃ for 130 min, centrifuge, wash the precipitate with deionized water until neutral, dry and set aside.
[0054] (2) The nanocellulose obtained in step (1) was ultrasonically dispersed in deionized water to prepare a nanocellulose suspension with a concentration of 2 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the solution was 1.0%. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution. The reaction was carried out at 60°C for 300 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried and set aside.
[0055] (3) Disperse 39.9 mg of the cationic modified nanocellulose obtained in step (2) in 30 ml of water, add 10 mg of curcumin, stir at room temperature for 30 h, and centrifuge to obtain the solubilized curcumin solution.
[0056] (4) Immerse the cotton fabric in the above cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30, keep it at 60℃ for 80 minutes, and after dyeing, take out the fabric, wash and dry it.
[0057] Example 6
[0058] (1) Slowly add microcrystalline cellulose to a 60% sulfuric acid solution with a mass-volume ratio of microcrystalline cellulose to sulfuric acid solution of 1:8.25 (g / mL). After reacting at 50℃ for 120 min, centrifuge, wash the precipitate with deionized water until neutral, dry and set aside.
[0059] (2) The nanocellulose obtained in step (1) was ultrasonically dispersed in deionized water to prepare a nanocellulose suspension with a concentration of 4 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the solution was 2.0%. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution. The reaction was carried out at 70°C for 240 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried and set aside.
[0060] (3) Disperse 60 mg of the cationic modified nanocellulose obtained in step (2) in 30 ml of water, add 10 mg of curcumin, stir at room temperature for 18 h, and centrifuge to obtain the solubilized curcumin solution.
[0061] (4) Immerse the cotton fabric in the above cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30, keep it at 65℃ for 70 minutes, and after dyeing, take out the fabric, wash and dry it.
[0062] Example 7
[0063] (1) Slowly add microcrystalline cellulose to a 62% sulfuric acid solution. The mass-volume ratio of microcrystalline cellulose to sulfuric acid solution is 1:7.75 (g / mL). After reacting at 55℃ for 100 min, centrifuge, wash the precipitate with deionized water until neutral, dry and set aside.
[0064] (2) The nanocellulose obtained in step (1) was ultrasonically dispersed in deionized water to prepare a nanocellulose suspension with a concentration of 5 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the solution was 2.5%. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution. The reaction was carried out at 75°C for 180 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried and set aside.
[0065] (3) Disperse 69.9 mg of the cationic modified nanocellulose obtained in step (2) in 30 ml of water, add 10 mg of curcumin, stir at room temperature for 12 h, and centrifuge to obtain a solubilized curcumin solution.
[0066] (4) Immerse the cotton fabric in the above cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30, keep it at 75℃ for 50 minutes, and after dyeing, take out the fabric, wash and dry it.
[0067] Example 8
[0068] (1) Slowly add microcrystalline cellulose to a 66% sulfuric acid solution with a mass-volume ratio of 1:7.25 (g / mL) of microcrystalline cellulose to sulfuric acid solution. After reacting at 60℃ for 90 min, centrifuge, wash the precipitate with deionized water until neutral, dry and set aside.
[0069] (2) The nanocellulose obtained in step (1) was ultrasonically dispersed in deionized water to prepare a nanocellulose suspension with a concentration of 6 g / L. The cationic modifier 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the solution was 3.0%. The pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution. The reaction was carried out at 80℃ for 90 min. After centrifugation, the precipitate was washed with deionized water until neutral, dried and set aside.
[0070] (3) Disperse 79.2 mg of the cationic modified nanocellulose obtained in step (2) in 30 ml of water, add 10 mg of curcumin, stir at room temperature for 6 h, and centrifuge to obtain the solubilized curcumin solution.
[0071] (4) Immerse the cotton fabric in the above cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30, keep it at 80℃ for 40 minutes, and after dyeing, take out the fabric, wash and dry it.
[0072] Example 9
[0073] Accurately weigh 10.25 mg of curcumin and place it in a 100 mL brown volumetric flask. Dilute to the mark with 80% anhydrous ethanol and mix well. Accurately measure 5.0 mL of the above solution into a 100 mL brown volumetric flask, dilute to the mark with 80% anhydrous ethanol, and mix well to obtain the stock solution. Accurately measure 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, and 10.0 mL of the curcumin stock solution into 10 mL brown volumetric flasks, dilute to the mark with 80% anhydrous ethanol, and mix well to obtain 1.0, 1.5, and 2 mg curcumin stock solutions, respectively. The absorbance of curcumin solutions with concentrations of 0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0 μg / mL was measured at 424 nm. A linear regression was performed on the absorbance (A) against the mass concentration (x, μg / mL) of the curcumin solution, yielding the regression equation A = 0.20543x + 0.0026. The supernatant of the nanocellulose-solubilized curcumin solutions obtained in Examples 1, 4-8, and Comparative Examples 1-2 after centrifugation was measured using a UV-1800 double-beam ultraviolet spectrophotometer, and the concentrations were calculated. Figure 2 .
[0074] Example 10
[0075] (1) A cationic modified nanocellulose solubilized curcumin solution was prepared according to the conditions of Example 1;
[0076] (2) Prepare a citric acid solution with a mass fraction of 35%. Weigh a certain amount of sodium hypophosphite and dissolve it in the citric acid solution. The mass fraction of sodium hypophosphite in the solution is 10%. Immerse the cotton fabric in the above mixed solution at a bath ratio of 1:25. Stir at room temperature for 15 minutes, dry at 80°C for 10 minutes, then wash thoroughly with deionized water and dry at 40°C to obtain the modified cotton fabric.
[0077] (3) Immerse the modified cotton fabric in the cationic modified nanocellulose solubilized curcumin solution obtained in step (1) at a bath ratio of 1:30, keep it at 70℃ for 60 min, after dyeing, take out the fabric, wash and dry it to obtain the dyed fabric modified with citric acid-sodium hypophosphite.
[0078] Example 11
[0079] (1) Prepare dyed fabric modified with citric acid-sodium hypophosphite according to the conditions of Example 10;
[0080] (2) Dissolve chitosan in a 2% acetic acid solution to prepare a 1% chitosan solution. Immerse the dyed cotton fabric obtained in step (1) into the chitosan solution. The mass ratio of the dyed cotton fabric to the chitosan solution is 1:100. After immersing for 15 minutes, dry at 150°C for 15 minutes.
[0081] Example 12
[0082] Washability test: The washability test was conducted according to the washing conditions in GB / T 3921.3-1997. Neutral soap was used as the detergent. The cotton fabric was placed in a container and the soap solution was prepared with 5 g / L neutral soap and 2 g / L anhydrous sodium carbonate, with a bath ratio of 1:50. The fabric was washed at 60℃ for 30 min. The cotton fabric was then removed, washed twice with deionized water, and dried at room temperature.
[0083] Color parameter testing: The dyed fabric was folded twice and the K / S value of the cotton fabric was measured using a Datacolor colorimeter under D65 light source and a 10° viewing angle. Each sample was tested four times at different locations, and the average value was taken. The results are shown in Table 1.
[0084] Table 1 K / S values of dyed fabrics
[0085]
[0086] The cationic modified nanocellulose of this invention has a significant solubilizing effect on curcumin. Figure 1 As can be seen from Table 1, the color depth (K / S value) of the obtained fabrics was higher than that of all Comparative Examples 1, 2, 3, 4 and 5. The main reason is that the microcrystalline cellulose (Comparative Example 1) and cationic modified microcrystalline cellulose have larger particle sizes (Comparative Example 2). After mixing and stirring with curcumin and filtering, most of the pigment is retained, the curcumin content in the solution is low, and the dyed fabric is light in color. In addition, the unmodified nanocellulose (Comparative Example 3) has a certain electronegativity. After binding to cotton fibers, it hinders the dyeing of negatively charged curcumin through electrostatic repulsion, resulting in light color and poor color fastness of the dyed fabric. When the content of cationic modifier in the cationic modification process of nanocellulose is low, the degree of cationization is insufficient, and the adsorption and binding capacity of curcumin is poor (Comparative Example 4). When the content of cationic modifier is high, all hydroxyl sites of nanocellulose are grafted and modified, reducing the ability of hydrogen bonding with hydroxyl groups of cotton fibers, thereby affecting the dyeing ability of the dye on cotton fabric (Comparative Example 5). After sulfuric acid hydrolysis, the particle size of microcrystalline cellulose is significantly reduced, and its dispersion stability in solution is significantly improved; even after filtration, the amount of residual nanocellulose in the solution is still relatively high; after cationic modification, its binding force with curcumin increases, the solubilizing effect is obvious, and the color of dyed fabrics is also significantly deepened. After citric acid treatment, the negative charge of cotton fabric is further enhanced, its binding force with cationic modified nanocellulose solubilizing curcumin increases, and the K / S value of dyed fabric increases (Example 10). Chitosan has good film-forming properties on cotton fabric and carries a certain positive charge. After treatment with chitosan, the adhesion of cationic modified nanocellulose-curcumin complex on cotton fabric is significantly increased, and the wash fastness of dyed fabric is significantly improved (Example 11).
[0087] The above embodiments are merely preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any changes, substitutions, modifications, etc., made by those skilled in the art without departing from the spirit and essence of the present invention should be within the protection scope of the present invention.
Claims
1. A method for improving the solubility of curcumin in water, characterized in that, The method steps are as follows: (1) After adding microcrystalline cellulose to sulfuric acid solution and reacting, centrifuge, wash the precipitate with deionized water until neutral, and dry to obtain nanocellulose; (2) The nanocellulose obtained in step (1) was ultrasonically dispersed in deionized water, a cationic modifier was added, the pH of the solution was adjusted to 12 with 4 mol / L sodium hydroxide solution, and centrifuged after reaction. The precipitate was washed with deionized water until neutral and dried to obtain cationic modified nanocellulose. The cationic modifier was 3-chloro-2-hydroxypropyltrimethylammonium chloride, and the mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the solution was 0.5-3%. (3) Disperse the cationic modified nanocellulose obtained in step (2) in water, add curcumin, stir at room temperature and centrifuge to obtain a cationic modified nanocellulose solubilized curcumin solution.
2. The method for improving the solubility of curcumin in water according to claim 1, characterized in that, In step (1), the mass fraction of sulfuric acid solution is 55-66%; the mass-volume ratio of microcrystalline cellulose to sulfuric acid solution is 1:9.75-1:7.25; the reaction temperature is 35-60℃; and the reaction time is 90-150 min.
3. The method for improving the solubility of curcumin in water according to claim 1, characterized in that, In step (2), the concentration of nanocellulose in deionized water is 1 g / L-6 g / L, the reaction temperature is 55-80℃, and the reaction time is 90-330 min.
4. The method for improving the solubility of curcumin in water according to claim 1, characterized in that, In step (3), the concentration of cationic modified nanocellulose in water is 1-2.67 g / L, the mass ratio of cationic modified nanocellulose to curcumin is 7.92:1-3:1, and the stirring time is 12-36 h.
5. An application of a cationic modified nanocellulose solubilized curcumin solution obtained by the method according to claim 1, characterized in that, The cationic modified nanocellulose solubilized curcumin solution is used for textile coloring.
6. The application of the cationic modified nanocellulose solubilized curcumin solution according to claim 5, characterized in that, Immerse the cotton fabric in a cationic modified nanocellulose solubilized curcumin solution at a bath ratio of 1:30, keep it at 55℃-80℃ for 30min-90min, and after dyeing, take out the fabric, wash and dry it.
7. A method for modifying cotton fabrics, characterized in that, The modification method is as follows: a citric acid solution with a mass fraction of 35% is prepared, sodium hypophosphite is weighed and dissolved in the citric acid solution, the mass fraction of sodium hypophosphite in the citric acid solution is 10%, cotton fabric is immersed in the above mixed solution at a bath ratio of 1:25, stirred at room temperature for 15 min, dried at 80℃ for 10 min, then thoroughly washed with deionized water, and dried at 40℃ to obtain modified cotton fabric; then the modified cotton fabric is immersed in the cationic modified nanocellulose solubilized curcumin solution obtained by the method described in claim 1 at a bath ratio of 1:30, kept at 55℃-80℃ for 30 min-90 min, after dyeing, the fabric is taken out, washed with water and dried to obtain citric acid-sodium hypophosphite modified dyed cotton fabric.
8. A method for fixing the color of dyed cotton fabric, characterized in that, Chitosan was dissolved in a 2% (w / w) acetic acid solution to prepare a 1% (w / w) chitosan solution. The citric acid-sodium hypophosphite modified dyed cotton fabric obtained by the method described in claim 7 was immersed in the chitosan solution. The mass ratio of the dyed cotton fabric to the chitosan solution was 1:
100. After immersion at room temperature for 15 min, the fabric was dried at 150°C for 15 min.
Citation Information
Patent Citations
Cationic dyes and uses thereof
CN118574858A